Developing and Validating a Prognostic Model for Mortality in Patients with Heart Failure - Muhammad-Kamal, Habibullah (2021)
Objectives: Develop and validate a prognostic model for all-cause mortality in patients diagnosed with Heart Failure. Also, to stratify mortality rates of patients diagnosed with Heart Failure, by BMI.